+0  
 
0
160
1
avatar

Let \(k, a_2, a_3\) be a geometric sequence with common ratio \(p \neq 1,\) and let \(k, b_2, b_3\) be a geometric sequence with common ratio \(r \neq 1.\) If\(a_3-b_3=3(a_2-b_2)\)and \(p \neq r,\) then find \(p + r.\)

 Jan 24, 2022
 #1
avatar+23200 
+1

a2  =  kp          a3  =  kp2          b2  =  kr          b3  =  kr2

 

a3 - b3  =  3(a2 - b2)     --->     kp2 - kr2  =  3(kp - kr)

                                               k(p2 - r2)  =  3k(p - r)

                                         k(p + r)(p - r)  =  3k(p - r)

Cancel:                                          p + r  =  3

 Jan 24, 2022

34 Online Users

avatar
avatar
avatar